Comparison Analysis of Cost and Time Forming Conventional Method With Semi-System Method for Column Namira Hotel Surabaya - Algerian Kusuma (NAROTAMA UNIVERSITY, Indonesia, 2022)
In the implementation of project activities, careful steps are needed and the determination of the right implementation method to obtain cost and time efficiency. In general, there are 3 types of formwork, namely conventional formwork, semi-system formwork, and system formwork. The difference between the three types can be seen from the material used. This study aims to determine the comparison of formwork in terms of method, cost and time in the construction of the Namira Hotel project located on Jl. Pagesangan Surabaya which consists of 9 floors. The cost of formwork is usually between 35% to 60% or more of the total construction cost. Material requirements are usually referred to as the calculation of the volume of work. The volume of a formwork work depends on the planned area. The duration needed to complete a job is influenced by the worker. So in order to determine the success of a project, the factors that must be considered are in terms of labor productivity and the number of workers. In the construction of Hotel Namira Surabaya, the cost of conventional column formwork was IDR 376,052,918.80 and for semi-column formwork it was IDR 214.624.700,00 where the duration of semi-system formwork was faster than conventional formwork.